ADVANCES IN LEGAL EDUCATION: THE ROLE OF LAW CLINICS IN PROMOTING CONSTITUTIONAL VALUES, HUMAN RIGHTS, AND PROFESSIONAL EXCELLENCE (USING THE EIU LAW CLINIC AS AN EXAMPLE) - Jomardyan, Nune; Apresyan, Zohrak; Tevosyan, Lia (Bulletin of Yerevan University C: Jurisprudence, 2026)
This article discusses the current state of legal education, highlighting the gap between theoretical instruction and the development of practical skills. While universities tend to overemphasize theoretical knowledge, recent educational reforms - such as the Bologna Process - sometimes undermine the understanding of fundamental legal theories and values essential for the professional development of future lawyers. The relevance of this study lies in the urgent need to align legal education with the demands of human rights protection, the promotion of social justice, and the elimination of discrimination. The aim of the study is to propose a reform model that bridges the gap between theory and practice by integrating legal clinics into the curriculum. The authors argue that legal clinics serve as effective educational tools, allowing students to engage with real cases, critically assess the legal system, and develop the skills necessary for legal practice. The findings of the study show that clinics not only enhance students’ practical abilities but also foster a deeper understanding of the ethical and social dimensions of legal work. This study contributes to the discourse on legal clinics as a model of experiential education and is also considered a strategy for improving the training of legal professionals to better meet the needs of contemporary society.